(untitled) (Bangladesh Journal of Medical Microbiology, 2010)
In order to monitor changes in the etiologic bacterial agents and as well as antimicrobial resistance of urinary pathogens between five years period and over several years, urinary culture and sensitivity result of patients attending the outpatient departments of Bangabandhu Sheikh Mujib Medical University (BSMMU) in 2003 and in 2008 were analyzed retrospectively. In 2003 and 2008, 668 and 715 cultures respectively were reviewed. The frequency of Escherichia coli dropped significantly in the outpatient clinics from 60.02% to 51.75%. The frequency of Klebsiella spp increased considerably. The frequency of Enterobacter spp. Enterococci spp and Acenatobacter collectively increased from 25.15 to 31.04 (p<0.0001). A significant rise in the resistance of Escherichia coli to gentamicin and ciprofloxacin (p<0.0001) was documented. Urinary pathogens also demonstrated increased resistance to Nalidixic acid and Cefotaxime. In contrast Amoxycillin, Cephradine (p<0.0001), Cotrimoxazole (p<0.0001), Mecilinam (p<0.0001), Ceftriaxone (p<0.0001). Nitrofurantoin, Ceftazidime, Cefuroxime, Amikacin and Netilmicin showed consistent sensitivity. Ciprofloxacin showed increase in resistance against Enterococci and Klebsiella. The changing etiologic agents of urinary tract infections and the increasing resistance of organisms clearly dictate regular monitoring and modification of empirical therapy are required. Bangladesh J Med Microbiol 2010; 03 (02): 9-12